2012
DOI: 10.1007/s00059-012-3634-9
|View full text |Cite
|
Sign up to set email alerts
|

Einfluss von Training auf Leistung und Gesundheit im mittleren Lebensalter

Abstract: Performance losses in middle age are often attributed to biological ageing. Running-time analyses in long-distance runners aged 20-80 years (n > 500,000) show that in fact no significant performance reductions occur before the age of 54 years. Moreover, further investigations carried out in the context of the PACE project (http://www.dshs-koeln.de/en/pace) reveal that performance losses in middle age are primarily caused by unhealthy lifestyle and lack of training. The increasing number of overweight, untraine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…9 Higher BMI and lack of routine aerobic activity were associated with poor physical performance. [25][26][27] Therefore, it is not surprising that we found an association between BMI >25 and routine exercise and fatigue in our study. However, a study performed by Hasegawa et al in Japan found a positive relationship between the rescuer performance and its weight; suggesting a rotation every one minute when the rescuer belongs to the light weight group.…”
Section: Discussionsupporting
confidence: 52%
“…9 Higher BMI and lack of routine aerobic activity were associated with poor physical performance. [25][26][27] Therefore, it is not surprising that we found an association between BMI >25 and routine exercise and fatigue in our study. However, a study performed by Hasegawa et al in Japan found a positive relationship between the rescuer performance and its weight; suggesting a rotation every one minute when the rescuer belongs to the light weight group.…”
Section: Discussionsupporting
confidence: 52%
“…An argument for running and jogging long distances could come from the long-term follow-up of individual long-distance runners, who even in their eighties demonstrated little or no loss of exercise capacity, whereas losses of function and capacity have been experienced in individuals with a predominant sedentary lifestyle [23].…”
Section: Main Topicmentioning
confidence: 99%
“…A growing body of evidence supports the health benefits of regular exercise in the aging population. 1 – 4 As a result, there is a universal acceptance of the concept that the overall benefits of exercise outweigh the risks of participation. 5 8 However, the occasional media reports of runners dying suddenly while competing in endurance events bring to the forefront the question of how to screen individuals for risk of complications related to participation.…”
Section: Introductionmentioning
confidence: 99%